Students' Perceptions of Using Twitter for Learning in Social Work Courses. Issue 1 (2nd January 2017) - Anthony, Becky; Jewell, Jennifer R.
ABSTRACT: Incorporating social media into social work education is on the rise. Yet little research exists on the outcomes of social media in the classroom. This article examines results from a study of students' perceptions of utilizing Twitter in which 198 undergraduate and graduate students from 15 social work courses participated from January 2015 to May 2016. Results suggest that Twitter can serve as a learning tool through resource sharing, current event awareness, and advocacy efforts and by facilitating the development of connections among students, professionals, and faculty members. Further discussion of these findings and implications for social work practice are provided.